Hierà kalá : images of animal sacrifice in archaic and classical Greece - Van Straten, F. T. (Religions in the Graeco-Roman World, 1995)
Hierà kalá presents a collection, analysis and interpretation of the representations of animal sacrifice from ancient Greece. The Archaic and Classical material is dealt with comprehensively. Later evidence is adduced more selectively, for the sake of comparison. All aspects of Greek sacrifice that are (or appear to be) represented in the iconographical material are treated in depth; interpretations are based on a combined study of the archaeological, the epigraphical and the literary data. Full catalogues of vase paintings and votive reliefs with depictions of sacrifice are included. A generous selection of these are illustrated in more than 200 figures.